Densitas dan Morfologi Stomata Daun Pterocarpus indicus di Jalan Arif Rahman Hakim dan Kampus ITS, Surabaya - Dhimas Wildan Humami; Puput Anggie Widhiarti Sujono; Iska Desmawati (Rekayasa, 2020)
The relationship between physiological and environmental factors can affect the anatomical structure and morphology of stomata as organs that important to exchange carbon gas, oxygen, and water vapor as well as organs that are directly exposed to polluted environments that can inhibit the photosynthesis process of plant leaves. The purpose of this study was to determine differences in stomata density and morphology of  Pterocarpus indicus leaves at locations suspected of having high pollution exposure and low pollution exposure. This study uses the leaf of Pterocarpus indicus as a type of plant that is often exposed to pollution. The leaf sampling method was carried out with 3 replications in the area of Arif Rahman Hakim Street and Taman Benzena, ITS Surabaya as a comparison of areas estimated to have high and low pollution exposure. Sampling using the abaxial side of the leaf by using the imprint method. Calculation of density is done by unit mm2 of leaf area under normal, closed, and abnormal stomata morphological conditions. The results obtained from the observation of stomata density in Taman ITS Benzena Surabaya are 32,502 stomata/mm2 were opened, 65,004 stomata/mm2 closed, and 13,630 stomata/mm2 abnormal, while in the area of Arif Rahman Hakim Street, Sukolilo, Surabaya as a sample location assuming the pollution is 46,132 stomata/mm2 were opened, 78,634 stomata/mm2 closed and 13,630 stomata/mm2 abnormal.